The Role of Discipline and Time Management in Improving Student Achievement in Sports - Siska Aprelyani (Siber International Journal of Sport Education, 2025)
Literature Review the role of discipline and time management in improving student achievement is a scientific article with the aim of analyzing whether student achievement plays a role in discipline and time management. The method examines various studies, articles, and books that are relevant to the topic discussed. The results of this article are: 1) Discipline plays a role in Student Achievement; 2) Time Management plays a role in Time Management. Apart from these 2 exogenous variables that affect the endogenous variable of Student Achievement, there are still many other factors including learning interest, school environment, learning outcomes.